Synthesis and Enhancement of Thermal Conductivity of Surfactant Free MWCNTs-Jatropha Oil-based Nanofluid - Rehman, W.U. (Institute of Physics Publishing, 2020)
Thermal conductivity enhancement of multi-walled carbon nanotubes (MWCNTs) based nanofluids received the attention of many researchers due to its remarkable thermal properties. However, the synthesis of surfactant-free multi-walled carbon nanotubes based nanofluids with higher dispersion stability to maintain a trade-off between its dispersion stability and thermophysical properties is still a challenge. In this research, a surfactant-free multi-walled carbon nanotube and Jatropha seed oil-based nano-dispersion are prepared via one-step method and subjected to experimental determination of thermal conductivity within the temperature range of (25 °C - 65 °C) and nanoparticle volume fraction range of (0.2 wt. - 0.8 wt.). The prepared nanofluid found to be highly stable for long time and its thermal conductivity enhancement was found to be 6.76. © Published under licence by IOP Publishing Ltd.